The effectiveness promotional strategy of Amanah Saham Nasional Berhad (ASNB) unit trust - Nor Hassin, Norhuwaina (2011)
The main objective of this research was to explore the effective Amanah Saham Nasional Berhad (ASNB) unit trust promotional strategies towards Malaysian. The respondents of this study were randomly selected from public area at Pemodalan Nasional Berhad Jalan Tun Razak, Kuala Lumpur. One hundred questionnaires had been distributed among those respondents. The researcher had used convenience sampling as the sampling technique. The questionnaire was design to the selected respondents which they were asked varieties of questions regarding their perception to the Amanah Saham Nasional Berhad (ASNB) promotional strategies. The process of analyzing and interpreting data has been presented with tables using methods such as frequency distribution and correlation.